The Effect of Environmental, Social, and Governance Factors on Banks’ Financial Performance: The Mediating Role of Organizational Innovation and Competitive Advantage - Nhung, Vu Cam (International Journal of Economics and Financial Issues, 2025)
This study analyses the impact of ESG practice on the financial performance of banks in Ho Chi Minh City (HCMC) by highlighting the mediating roles of competitive advantage and innovation. Since the upsurge in the level of competition in the banking sector in HCMC, proper information on how these factors affect financial outcomes should be known to ensure long-term success. Data used in this study were obtained from 347 employees working in different banks in HCMC collected through convenient sampling methodology. The SmartPLS software was used to check the research model and hypotheses. The results indicate that the elements of ESG, environmental, social, and governance positively influence the financial performance of banks in mediation through competitive advantage and innovation. Specific results indicate that other than building the brand of the bank, a strong ESG framework enhances the competitive advantage and innovation of the bank all culminating in enhanced financial outcomes. This gives much of what is needed to know-how veritable sustainable business practice may increment profitability within the banking trade, importantly within emergent markets as in HCMC. The learnings of this study shall be thought precious by both academic minds and professionals. This shows that including ESG practice within business strategy shall improve efficiency in operations, increase customer satisfaction, and draw ethical investors. Therefore, banks in HCMC would use ESG practice to better their market position amidst an increasing competitive setting by promoting sustainability.